SATELLITESTRUCTURE REDUCING DAMAGE RESEARCHAND STIMULATION BASEDON ELASTIC IMPACT - ZHAO Hua; YU Kuai; Fan Ning (Jixie qiangdu)
Usually satellite is under complex dynamic load during the launch phase,it’s easy to cause satellitestructure damageto influence spacecraftmission. Mechanical environment tests show that spacecraftstructure damage always occurs because of larger acceleration response of equipment such as large mass or high center of mass,and affecttedthe project development.Difference from the usual engineering solutions,a method based on gap elastic impactting is studiedto reducing damage. By constructing mechanical model,simulation and analysis has been done to a designated parameter structurepanel and equipment,results show that the methed as one of solutions of lower damage is valid to reducing defomation and load located at connection between equipment andstructure.